The Effects of Beverage Specific Alcohol Sale on Liver Cirrhosis Mortality in Russia - Razvodovsky YE (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2015)
Background: Liver cirrhosis is a major cause of deaths in many developed countries. There is evidence that beverage preference may have modifying influence on liver cirrhosis risk independently of the amount of alcohol consumed. The aim of this study was to examine the relation between the consumption of different beverage types and liver cirrhosis mortality rates in Russia. Method: Time-series analytical modeling techniques were used to examine the relation between the sale of different alcoholic beverages (vodka, wine, beer) and age-standardized male and female liver cirrhosis mortality data for the period 1970-2005. Results: Total alcohol sale is a statistically significant associated with both male and female liver cirrhosis mortality rates, implying that a 1-litre increase in per capita alcohol sale is associated with an increase in male mortality of 17.2% and female mortality of 5.3%. The analysis also suggests that of the three beverages (vodka, beer and wine) vodka alone was associated with liver cirrhosis mortality in Russia. The estimated effects of vodka sales on the liver cirrhosis mortality rate are clearly statistically significant for both sexes: a 1 liter increase in vodka sale would result in a 37.6% increase in the male liver cirrhosis mortality rate and in 9.3% increase in female mortality rate. Conclusions: The findings from present study support the substantial literature which demonstrates a close link between alcohol consumption and liver cirrhosis mortality at aggregate level, and most important, suggests that this relationship is mediated by beverage preference.